HSV-2 Cellular Programming Enables Productive HIV Infection in Dendritic Cells - Crisci, Elisa; Svanberg, Cecilia; Ellegård, Rada; Khalid, Mohammad; Hellblom, Julia; Okuyama, Kazuki; Bhattacharya, Pradyot; Nyström, Sofia; Shankar, Esaki M.; Eriksson, Kristina; Larsson, Marie (Frontiers in Immunology, 2019)
Genital herpes is a common sexually transmitted infection caused by herpes simplex virus type 2 (HSV-2). Genital herpes significantly enhances the acquisition and transmission of HIV-1 by creating a microenvironment that supports HIV infection in the host. Dendritic cells (DCs) represent one of the first innate cell types that encounter HIV-1 and HSV-2 in the genital mucosa. HSV-2 infection has been shown to modulate DCs, rendering them more receptive to HIV infection. Here, we investigated the potential mechanisms underlying HSV-2-mediated augmentation of HIV-1 infection. We demonstrated that the presence of HSV-2 enhanced productive HIV-1 infection of DCs and boosted inflammatory and antiviral responses. The HSV-2 augmented HIV-1 infection required intact HSV-2 DNA, but not active HSV-2 DNA replication. Furthermore, the augmented HIV infection of DCs involved the cGAS-STING pathway. Interestingly, we could not see any involvement of TLR2 or TLR3 nor suppression of infection by IFN-β production. The conditioning by HSV-2 in dual exposed DCs decreased protein expression of IFI16, cGAS, STING, and TBK1, which is associated with signaling through the STING pathway. Dual exposure to HSV-2 and HIV-1 gave a proteolytic degradation of several HIV-1 restriction factors, especially SAMHD1, TREX1, and APOBEC3G. Activation of the STING pathway in DCs by exposure to both HSV-2 and HIV-1 most likely lead to the proteolytic degradation of the HIV-1 restriction factors SAMHD1, TREX1, and APOBEC3G, which should release their normal restriction of HIV infection in DCs. This released their normal restriction of HIV infection in DCs. We showed that HSV-2 reprogramming of cellular signaling pathways and protein expression levels in the DCs provided a setting where HIV-1 can establish a higher productive infection in the DCs. In conclusion, HSV-2 reprogramming opens up DCs for HIV-1 infection and creates a microenvironment favoring HIV-1 transmission.